2006
DOI: 10.1074/jbc.m509480200
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of Tyrosine 92 Mediates the Activation of Rat Microsomal Glutathione S-Transferase by Peroxynitrite

Abstract: There is increasing evidence that protein function can be modified by nitration of tyrosine residue(s), a reaction catalyzed by proteins with peroxidase activity, or that occurs by interaction with peroxynitrite, a highly reactive oxidant formed by the reaction of nitric oxide with superoxide. Although there are numerous reports describing loss of function after treatment of proteins with peroxynitrite, we recently demonstrated that the microsomal glutathione S-transferase 1 is activated rather than inactivate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 28 publications
0
37
0
1
Order By: Relevance
“…MGST1 as a constitutively expressed enzyme, catalyzes the reaction of glutathione with a range of xenobiotic and endogenous electrophiles, reduces the products from lipid peroxidation, and serves mainly as an important detoxication enzyme in the liver [14,30,31]. The expression of MGST1 is relatively stable.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…MGST1 as a constitutively expressed enzyme, catalyzes the reaction of glutathione with a range of xenobiotic and endogenous electrophiles, reduces the products from lipid peroxidation, and serves mainly as an important detoxication enzyme in the liver [14,30,31]. The expression of MGST1 is relatively stable.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to the cytosolic GSTs, an important characteristic of MGST1 lies in the posttranslational modi cations on the enzyme regulating its catalytic activities. Under physiological conditions, MGST1 displays very limited activities; however, a variety of posttranslational modi cations including alkylation, nitration, dimerization, etc., could signi cantly enhance its activities and cause enzyme activation [14,15]. Peroxynitrite (ONOO -) is one of the RNS and can regulate many protein functions via posttranslational modi cations [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, nitration at Tyr92 was shown to be critical in functional change as another example of gain in protein function. This conclusion was evidenced by site directed mutagenesis of each Tyr residue of GST-1, overexpression of each GST-1 mutant in LLC-PK1 cells, and then exposure to peroxynitrite followed by monitoring its activity [41]. The activation of GST-1 nitrated at Tyr92 would improve the antioxidant defense.…”
Section: Functional Consequences Of Protein Nitration In Acute Andmentioning
confidence: 99%
“…A characteristic of rat liver MGST1 is that covalent modification (e.g., alkylation by N-ethylmaleimide) of its single cysteine residue (Cys-49) results in a marked increase in enzyme activity. Oxidative modification of Cys-49 also results in increased enzyme activity, and recent data from our laboratory have demonstrated that in addition to oxidative stress, nitrosative stress increases MGST1 activity by tyrosine nitration of Tyr-92 and, to a lesser extent, by nitrosation of Cys-49 (Ji et al, 2002(Ji et al, , 2006Ji and Bennett, 2003). In the present study, our goal was to compare GTN biotransformation by the microsomal and cytosolic GSTs to assess the effect of various modifications of MGST1 on GTN biotransformation and to assess whether MGST1 activity or expression is altered in GTN-tolerant animals.…”
mentioning
confidence: 99%